2022
DOI: 10.1002/smll.202201943
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromic Cs2AgBiBr6 Single Crystal with Decreased Band Gap through Order‐Disorder Transition

Abstract: Lead‐free Cs2AgBiBr6 double perovskite is considered to be a promising alternative to the traditional lead‐based analogues due to its long carrier lifetime, high structural stability, and non‐toxicity. However, the large band gap limits its absorption of visible light, which is not conducive to further optoelectronic applications. Herein, a thermochromic strategy is reported to decrease the band gap of Cs2AgBiBr6 by approximately 0.36 eV, obtaining the smallest reported band gap of 1.69 eV under ambient condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Together with these three modes, we observed a broad peak (multiphoton peaks) at 355 cm –1 , which corresponds to the second order of the A 1g mode at 185.1 cm –1 , respectively . As a result of the substantial difference in electronegativity between Ag–Br (1.03) and Bi–Br (0.94), it was suggested in the literature that the bonding strength of Ag–Br type bonds is significantly higher than that of Bi–Br bonds, allowing it to be treated as a discrete-like entity (0D electronic dimensionality). …”
mentioning
confidence: 70%
“…Together with these three modes, we observed a broad peak (multiphoton peaks) at 355 cm –1 , which corresponds to the second order of the A 1g mode at 185.1 cm –1 , respectively . As a result of the substantial difference in electronegativity between Ag–Br (1.03) and Bi–Br (0.94), it was suggested in the literature that the bonding strength of Ag–Br type bonds is significantly higher than that of Bi–Br bonds, allowing it to be treated as a discrete-like entity (0D electronic dimensionality). …”
mentioning
confidence: 70%
“…[ 39 ] Later, Huang and co‐workers observed that simply postannealing a Cs 2 AgBiBr 6 crystal at 400 °C for 24 h could decrease the bandgap to around 1.69 eV (Figure 11i). [ 40 ] These results imply the thermal energy may be the driving force to overcome the order‐to‐disorder transition barrier to achieve partially disordered Cs 2 AgBiBr 6 crystals. It is noted that a direct evidence of atomic rearrangement is still missing.…”
Section: Challenges and Efforts In Hdps Solar Cellsmentioning
confidence: 99%
“…Recent reports indicate that this may be possible using single‐Cs 2 AgBiBr 6 crystals or polycrystalline Cs 2 AgBiBr 6 with significantly lower defects. [ 5,7,31 ] Using the realistic case of asymmetric diffusion lengths typically reported for polycrystalline Cs 2 AgBiBr 6 thin films, the bifacial architecture may exhibit a significantly improved PCE compared to the standard architecture. This result confirms that the asymmetric carrier diffusion length of Cs 2 AgBiBr 6 is highly detrimental to its PV efficiency.…”
Section: Bifacial Architecturementioning
confidence: 99%
“…[ 3 ] In contrast to lead (Pb)‐based perovskite materials, Cs 2 AgBiBr 6 denotes another family of perovskite structures that are relatively stable and contain no toxic elements. [ 4 ] These beneficial characteristics, in conjunction with low‐cost solution processing, mean that Cs 2 AgBiBr 6 has the potential not only for PV applications, but also in other fields such as X‐ray detectors, [ 5 ] photocatalysts, [ 6 ] smart windows, [ 7 ] and optical switching memory. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%